Electrodiagnosis of Retinal Disease - Miyake, Yozo. (Springer Japan : Imprint: Springer, 2006)
Soon it will be time for me to retire from my position as professor of o- thalmology in the Department of Ophthalmology, Nagoya University School of Medicine. I have therefore decided to summarize my expe- ence of more than 30 years of studies on the clinical electrophysiology of vision. These studies were performed in our department through the hard work and good ideas of many co-workers,and the chapters of this book cover the rationale and results of our studies. Because excellent textbooks on clinical electroretinography already exist, my wish is not to write another textbook; instead,this book is in the form of essays that include my beliefs and philosophy on the clinical electrophysiology of vision. As such,this book does not include every clinical disease but only those that we have identi?ed or studied in detail. In addition to full-?eld electroretinography (ERG),we developed the techniques and instrumentation to record focal macular ERG more than two decades ago. Using these techniques, we were able to determine several new physiological properties of the normal macula, many new pathophysiological mechanisms of known diseases,and some new cli- cal entities with unique functional properties. Fortunately,the recent advances of macular surgery and imaging are such that the macular con?guration can easily be determined. During the process of surgery,we have obtained considerable information on the c- relation of macular function and macular morphology using focal macular ERGs and optical coherence tomography (OCT).